Heterologous avian system for quantitative analysis of Syncytin-1 interaction with ASCT2 receptor - Štafl, Kryštof; Trávníček, Martin; Kučerová, Dana; Pecnová, Ľubomíra; Krchlíková, Veronika; Gáliková, Eliška; Stepanets, Volodymyr; Hejnar, Jiří; Trejbalová, Kateřina (Retrovirology, 2021)
BACKGROUND: Human Syncytin-1 is a placentally-expressed cell surface glycoprotein of retroviral origin. After interaction with ASCT2, its cellular receptor, Syncytin-1 triggers cell-cell fusion and formation of a multinuclear syncytiotrophoblast layer of the placenta. The ASCT2 receptor is a multi-spanning membrane protein containing a protruding extracellular part called region C, which has been suggested to be a retrovirus docking site. Precise identification of the interaction site between ASCT2 and Syncytin-1 is challenging due to the complex structure of ASCT2 protein and the background of endogenous ASCT2 gene in the mammalian genome. Chicken cells lack the endogenous background and, therefore, can be used to set up a system with surrogate expression of the ASCT2 receptor. RESULTS: We have established a retroviral heterologous chicken system for rapid and reliable assessment of ectopic human ASCT2 protein expression. Our dual-fluorescence system proved successful for large-scale screening of mutant ASCT2 proteins. Using this system, we demonstrated that progressive deletion of region C substantially decreased the amount of ASCT2 protein. In addition, we implemented quantitative assays to determine the interaction of ASCT2 with Syncytin-1 at multiple levels, which included binding of the soluble form of Syncytin-1 to ASCT2 on the cell surface and a luciferase-based assay to evaluate cell-cell fusions that were triggered by Syncytin-1. Finally, we restored the envelope function of Syncytin-1 in a replication-competent retrovirus and assessed the infection of chicken cells expressing human ASCT2 by chimeric Syncytin-1-enveloped virus. The results of the quantitative assays showed that deletion of the protruding region C did not abolish the interaction of ASCT2 with Syncytin-1. CONCLUSIONS: We present here a heterologous chicken system for effective assessment of the expression of transmembrane ASCT2 protein and its interaction with Syncytin-1. The system profits from the absence of endogenous ASCT2 background and implements the quantitative assays to determine the ASCT2-Syncytin-1 interaction at several levels. Using this system, we demonstrated that the protruding region C was essential for ASCT2 protein expression, but surprisingly, not for the interaction with Syncytin-1 glycoprotein.
Keywords: vedlejší histokompatibilní antigeny; Gene Products, env; genové produkty env; Pregnancy; Humans; Chickens; Microscopy, Confocal; Minor Histocompatibility Antigens; Placenta; Female; konfokální mikroskopie; lidé; těhotenské proteiny; zvířata; Fluorescence; buněčné linie; kur domácí; ženské pohlaví; Cell Line; těhotenství; Pregnancy Proteins; fibroblasty; fluorescence; Animals; transportní systém ASC pro aminokyseliny; placenta; Amino Acid Transport System ASC; Fibroblasts